The Influence Of Celebrity Endorsement On Social Media On Consumer Intention To Buy (Consumer study of Diamore Store Yogyakarta Branch) - Anafiah, Dhurotul; Harahap, Ridho Satrio; Wibisono, Dimas; Syah, Toufan Aldian (DAS Institute, 2022)
This study aims to determine the respondents' responses to the influence of Vis CAP partially and simultaneously on social media consumer interest. This study used a questionnaire method distributed through social media using Google form, using a purposive sampling type, with 100 respondents. The type of research used is quantitative research and uses a descriptive analysis approach. Then the data analysis was carried out by instrument testing using validity and reliability tests, classical assumption tests, and multiple linear regression tests, to test hypotheses through the R2 termination coefficient test, F test, and T-test. The test results after fulfilling the validity and reliability tests with SPSS25 tools produce the following regression equation: Y = 4.264 + 0.337 (visibility) + 0.142 (credibility) + 0.311 (attraction) + 0.752 (power) + e. The partial and simultaneous analysis results positively or significantly influence consumer buying interest in social media users. Simultaneous research results Vis CAP has a significant effect seen from the results of the coefficient of determination of 57.8%, while other variables outside the research model influence the remaining 42.2%.